Review on flow separation control: effects of excitation frequency and momentum coefficient - Abdolahipour, Soheila (Frontiers in Mechanical Engineering, 2024)
This paper presents a comprehensive review of the studies and research conducted on flow separation control on lifting surfaces. In this paper, two critical parameters, namely, the momentum coefficient and excitation frequency, that significantly impact flow separation control are analyzed in detail. Through a comprehensive literature review, experimental and numerical studies are examined in order to gain insight into the underlying mechanisms of momentum injection and excitation frequency on the shear layer and wake dynamics and to quantify the impact of these parameters on the flow separation control. Effective flow control on lifting surfaces can modify the streamlines and pressure distribution, thereby increasing their aerodynamic efficiency. This paper focuses on the control of flow separation on airfoils, with particular attention paid to the benefits of such control, including lift enhancement, drag reduction, aerodynamic efficiency enhancement, performance enhancement, and other important features. This paper presents a review of studies that have employed blowing actuators, as well as zero net mass flux, plasma, and acoustic actuators, in order to provide an appropriate historical context for recent developments. The findings of this review paper will contribute to a better understanding of the optimal conditions for efficient flow separation control on lifting surfaces using unsteady excitation, which can have significant implications for improving the performance and efficiency of various aerodynamic applications. This paper aims to elucidate and emphasize the positive and negative aspects of existing research, while also suggesting new interesting areas for future investigation.